Legitimate target : a criteria-based approach to targeted killing - Guiora, Amos N., 1957- (New York : Oxford University Press, 2013)
In 'Legitimate Target: a Criteria-Based Approach to Targeted Killing', Amos Guiora proposes that targeted killing decisions must reflect consideration of four distinct elements: law policy, morality, and operational details, thus ensuring that it complies with principles of domestic and international laws.
Description based on online resource; title from home page (viewed on Apr. 29, 2013).
Includes index.
Keywords: Targeted killing; Targeted killing (International law); Targeted killing -- Moral and ethical aspects; Terrorism -- Prevention -- Government policy